Compound C enhances tau phosphorylation at Serine396 via PI3K activation in an AMPK and rapamycin independent way in differentiated SH-SY5Y cells. (23rd March 2018) - Majd, Shohreh; Koblar, Simon; Power, John
Highlights: Compound C increases p-tau (Ser 396 ) but not (Ser 262 ) in SH-SY5Y derived neurons. Compound C (10 μM) does not affect p-AMPK but decreases p-mTOR. LY294002, a specific PI3K inhibitor, blocks compound C-mediated increase of p-tau. Rapamycin does not affect p-tau and p-mTOR when AMPK activity is not changed. Abstract: Aggregation of hyperphosphorylated tau (p-tau) in the form of neurofibrillary tangles (NFT) is a main hallmark for Alzheimer's disease (AD). Activation of cellular metabolic axis, made of adenosine monophosphate kinase protein kinase (AMPK) and mammalian target of rapamycin (mTOR) have been implicated in generating tau pathology of AD. Thus, blocking either of these two proteins or both, are suggested as the future therapeutic approaches for AD. How and to what level these approaches could be applied, however are not entirely clear. By using Compound C (CC) in this study, we showed a substantial decrease in mTOR activity in a rapamycin-independent way without blocking AMPK. This decline in mTOR activity was accompanied by an increase in phosphoinositide 3 kinase (PI3K)/Akt activity and a parallel increase in p-tau (Ser 396 ) but not p-tau (Ser 262 ) in differentiated SH-SY5Y neuroblastoma cells. This elevation was blocked when the cells were treated with 15 μM of LY294002, a specific PI3K inhibitor, suggesting PI3K involvement in CC-mediated tau hyperphosphorylation at Ser 396 . For all groups the activity levels of glycogen synthase kinase-3β (GSK-3β), cyclin-dependent kinase-5 (cdk5) and protein phosphatase 2A (PP2A), the other main kinases and phosphatase responsible for tau phosphorylation/dephosphorylation remained unchanged. Collectively, our results demonstrate that rapamycin-independent blocking of mTOR enhances p-tau (Ser 396 ) in a PI3K-dependent way, suggesting the careful consideration of future therapeutic approaches for AD, which will be based on mTOR inhibition.